Effect of mosses and lichens on the elemental composition and dynamics of carbon in the water of thermokarst lakes - Manasypov, Rinat M. (2021)
The influence of the plant substrate on the formation of the elemental composition of water and the dynamics of carbon (DOC and CO2) in thermokarst lakes in the discontinuous permafrost zone of Western Siberia was studied. Mesocosm experiments were conducted during 3 weeks on large thermokarst lake waters interacting in 30-L tanks with the dominant ground vegetation (lichen Cladonia sp. аnd moss Sphagnum sp.). As a result of mesocosm experiments is that lichen is able to change the chemical composition of melt water more strongly than mosses. An increase in the DOC concentration upon contact with lichen shows a rapid increase in the DOC concentration (2–3 weeks) at a high substrate concentration. The increase in conductivity, DOC and SUVA254, and concentrations of CO2 and CH4 in lake water in the presence of moss and lichen in the first week of the experiment are within the range of values characteristic of natural thermokarst subsidence and lakes. Thus, the conducted field experiments on setting up mesocosms with the addition of the dominant vegetation of flat-hilly frozen bogs (mosses and lichens) can serve as experimental models of the formation of the elemental composition and the formation of dissolved greenhouse gases in thermokarst subsidence.